191k views
4 votes
Please help me, GodBless.

Please help me, GodBless.-example-1
User Siraj
by
4.5k points

2 Answers

4 votes

Answer:

The awnser is (-1,-1) i hope this helped you out

User Scott Bossak
by
4.8k points
5 votes

Answer:

(-1 , -1)

Explanation:

You can simply use the substitution method to solve for this system. For simplicity, let's substitute the second equation (y=x) into the first equation. Basically switch the y's for x's in the first equation.

Therefore you get:

-6x - 5x = 11

-11 x = 11

x = -1

Then use the second equation that you substitued in to solve for y (y=x):

y = x

y = -1

So the final point is (-1, -1)

User TheUturn
by
4.4k points